Effective Utilization of Web Based E-Office System in Payakumbuh High School of Technology - Delfianis, Neni; Mubara, Ilham; Amna, Amna; Budiarni, Rini; Noviarti, Noviarti (Universitas Gajah Putih, 2025)
Correspondence has defined as a written communication medium between private agencies and government agencies. It become the main reference for all activities within an agency. Payakumbuh High School of Technology (STTP) is one of the private universities in Payakumbuh City which still uses a manual system in managing data related to correspondence as it is prone to error. Therefore, a web-based e-Office system was built using the SLDC Waterfall method. The performance of the e-Office system is tested using GTMetrix. To determine the level of effective usage of the e-Offuce system at STTP, a research was conducted using quantitative methods which were analyzed based on the Technology Acceptance Model (TAM). From the results of testing the performance of the e-Office system, it is obtained a grade “A”, which states a “Very Good” performance. While the results of the research on the effectiveness of the e-Office system in STTP use obtained a value of 3.235, which can be interpreted that the system could be used “effectively” by users.